Intrinsically Stretchable Fuel Cell Based on Enokitake‐Like Standing Gold Nanowires. Issue 2 (28th November 2019) - Zhai, Qingfeng; Liu, Yiyi; Wang, Ren; Wang, Yan; Lyu, Quanxia; Gong, Shu; Wang, Joseph; Simon, George P.; Cheng, Wenlong
Abstract: Conventional fuel cells are based on rigid electrodes, limiting their applications in wearable and implantable electronics. Here, it is demonstrated that enokitake‐like vertically‐aligned standing gold nanowires (v‐AuNWs) can also serve as powerful platform for stretchable fuel cells by using ethanol as model system. Unlike traditional fuel cell electrodes, the v‐AuNWs have "Janus Morphology" on both sides of the film and also are highly stretchable. The comparative studies demonstrate that tail side exposed v‐AuNWs based stretchable electrodes outperform the head‐side exposed v‐AuNWs toward the electro‐oxidation of ethanol due to the direct exposure of high‐surface‐area nanowires to the fuels. Therefore, a stretchable fuel cell is fabricated utilizing tail side based interdigitated electrodes, where v‐AuNWs and Pt black modified v‐AuNWs serve as the anode and cathode, respectively. The as‐prepared stretchable fuel cell exhibits good overall performance, including high power density, current density, open‐circuit voltage, stretchability, and durability. Most importantly, a wearable fuel cell is also achieved by integrating tattoo‐like interdigitated electrodes with a thin layer of sponge as a fuel container, exhibiting good performance under various deformations (compression, stretching, and twisting). Such attractive performance in conjunction with skin‐like in‐plane design indicates its great potential to power the next‐generation of wearable and implantable devices. Abstract : A highly stretchable fuel cell is presented based on enokitake‐like vertically standing gold nanowires with good performance, it holds great potential to power the next‐generation of wearable and implantable devices.